Crystal structure of (E)-2-amino-4-methylsulfanyl-6-oxo-1-{[(thiophen-2-yl)methylidene]amino}-1,6-dihydropyrimidine-5-carbonitrile - Elgemeie, Galal H. (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, C(11)H(9)N(5)OS(2), a 1-thiophen-2-ylmethyleneaminopyrimidine derivative, displays an essentially planar C—NH(2) group. The conformation across the N=C bond linking the pyrimidine and thienyl groups is E. The pyrimidine and thienyl ring systems subtend an inter-planar angle of 42.72 (5)°. In the crystal, molecules are linked by N–H⋯N(nitrile) and N–H⋯O=C hydrogen bonds, forming chains parallel to the b axis.